The use of Chara spp. (Charales: Characeae) as a bioindicator of physico‐chemical habitat suitability for an endangered crayfish Austropotamobius pallipes in lentic waters. Issue 2 (3rd November 2017) - Beaune, David; Sellier, Yann; Lambert, Élisabeth; Grandjean, Frédéric
Abstract: Austropotamobius pallipes is an endangered decapod attracting much attention in freshwater conservation programmes. In some cases population transfers or reintroductions are carried out in lentic ecosystems such as ponds or quarries. Such conservation actions require rapid, low cost and powerful tools to census suitable habitat. Some species of the Characeae family ( Chara spp.), share ecological needs with A. pallipes and are proposed as bioindicators of suitable habitat. Chara species were tested, among other plants, as bioindicators, and to see whether Chara species are a stronger indicator than water chemistry. The Pinail Nature Reserve, with 3000 permanent ponds, is inhabited by white‐clawed crayfish probably introduced historically into ponds used for fish production. This allows a replicated study of suitable habitats where plant communities are bioindicators of crayfish presence. Crayfish presence is associated with Chara species (such as Chara aspera, Chara virgata, Chara fragifera, Chara polyacantha and Chara vulgaris ). Austropotamobius pallipes is present in ponds with Chara spp. ( N  = 10/10) while other ponds without crayfish are lacking charophytes (N = 1/23). Algae of the genus Chara are thus a simple and low‐cost additional tool for determining suitable habitat for crayfish introductions within enclosed waters protected from exotic invasive species and disease. Cladium mariscus also appears to be another useful bioindicator for crayfish habitat.